2012
DOI: 10.1242/jeb.071837
|View full text |Cite
|
Sign up to set email alerts
|

Body dynamics and hydrodynamics of swimming fish larvae: a computational study

Abstract: SUMMARYTo understand the mechanics of fish swimming, we need to know the forces exerted by the fluid and how these forces affect the motion of the fish. To this end, we developed a 3-D computational approach that integrates hydrodynamics and body dynamics. This study quantifies the flow around a swimming zebrafish (Danio rerio) larva. We used morphological and kinematics data from actual fish larvae aged 3 and 5days post fertilization as input for a computational model that predicted free-swimming dynamics fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 37 publications
8
93
1
Order By: Relevance
“…This may be due to the high inefficiency of paddling. Larval fish swim with a propulsive efficiency of around 0.3 (Li et al, 2012), which is about threefold greater than what we have found in most water boatmen (Fig. 10B).…”
Section: The Energetics Of Swimmingcontrasting
confidence: 63%
“…This may be due to the high inefficiency of paddling. Larval fish swim with a propulsive efficiency of around 0.3 (Li et al, 2012), which is about threefold greater than what we have found in most water boatmen (Fig. 10B).…”
Section: The Energetics Of Swimmingcontrasting
confidence: 63%
“…high circulation and 'jets'). Both vortices and accelerated velocities are hydrodynamic features associated with and directly related to zones of negative pressure in the fluid (Batchelor, 1973;Li et al, 2012), and, for the control lampreys, the gradual development of these hydrodynamic features gradually developed large negative pressure zones in the troughs of the traveling waves ( Fig. 9F; Gemmell et al, 2015).…”
Section: Pressure and Thrust Resulting From Different Hydrodynamic Comentioning
confidence: 99%
“…However, we have much less of an understanding of the mechanisms through which bending kinematics interact with adjacent fluids to enhance thrust. One effect of bending is that it enhances negative pressure regions of the fluid adjacent to the inflexion point of the bending appendage (Colin et al, 2012;Li et al, 2012;Nakata and Liu, 2012). This serves to accelerate more fluid than fluid around rigid propulsors, which enhances the momentum of the surrounding fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang and Kiørboe, 2011;Li et al, 2012;Liu et al, 1996;Van Wassenbergh et al, 2015a). CFD analyses can consider the fluid forces generated by complex geometries with fully resolved volumetric flow fields.…”
Section: Introductionmentioning
confidence: 99%